2000
DOI: 10.1128/aem.66.9.3784-3789.2000
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Diamondback Moth Resistance to Transgenic Broccoli Expressing High Levels of Cry1C

Abstract: A field-collected colony of the diamondback moth, Plutella xylostella, had 31-fold resistance to Cry1C protoxin of Bacillus thuringiensis. After 24 generations of selection with Cry1C protoxin and transgenic broccoli expressing a Cry1C protein, the resistance that developed was high enough that neonates of the resistant strain could complete their entire life cycle on transgenic broccoli expressing high levels of Cry1C. After 26 generations of selection, the resistance ratios of this strain to Cry1C protoxin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 40 publications
5
82
0
1
Order By: Relevance
“…Along the same lines, changes in these toxin binding sites in the insect would not be reflected in a large change in binding parameters. Such a situation may have occurred in strains of Plutella xylostella and S. exigua that are highly resistant to Cry1Ca, for which binding studies reported just a small change in binding capacity [17,35]. This theory is supported by the observation that lack of a cadherin-like receptor in a Cry1A-resistant strain of Heliothis virescens (YHD2) [36] hardly affects the detectable binding of Cry1Ab or Cry1Ac in the resistant strain [37].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Along the same lines, changes in these toxin binding sites in the insect would not be reflected in a large change in binding parameters. Such a situation may have occurred in strains of Plutella xylostella and S. exigua that are highly resistant to Cry1Ca, for which binding studies reported just a small change in binding capacity [17,35]. This theory is supported by the observation that lack of a cadherin-like receptor in a Cry1A-resistant strain of Heliothis virescens (YHD2) [36] hardly affects the detectable binding of Cry1Ab or Cry1Ac in the resistant strain [37].…”
Section: Discussionsupporting
confidence: 59%
“…Toxin was eluted from the column by increasing the NaCl concentration. For iodine labelling of Cry1Ca, an additional purification step was performed, following the procedure described in Zhao et al [17], to remove adsorbed protoxin fragments that block iodination.…”
Section: Mutagenesis and Protein Isolationmentioning
confidence: 99%
“…In fieldderived populations of the diamondback moth, resistance to Cry1Ac did not correspond to monogenic inheritance in a population from Malaysia (30), and two different genes that confer resistance to Cry1Ab were present in a population originating from the Philippines (10). Direct tests of monogenic inheritance of Cry1C resistance in a P. xylostella population originating from New York suggested that significant deviations between observed and expected mortalities were the result of nonadditive polygenic inheritance or experimental error (44), and further tests indicated that there might be polygenic inheritance (45).…”
Section: Discussionmentioning
confidence: 99%
“…A field-collected population (Cry1C-Sel) from South Carolina displayed 31-fold resistance to Cry1C. Continuous laboratory selection, using first Cry1C protoxin, and in later generations transgenic broccoli expressing high levels of Cry1C, increased resistance to 12,400-fold (in neonates) and 63,100-fold (in second instars) after 26 generations (Zhao et al 2000). A Malaysian colony (SERD3) was reported to be resistant to both Btk and Bta .…”
Section: Bacteriamentioning
confidence: 99%